Controllable synthesis of silver nanoparticles using an acoustofluidic micromixer based on ultrasonic vibration. (June 2022) - Liu, Guojun; Wang, Meng; Zhu, Duanyi; Liu, Qiang; Dong, Luntao; Wang, Conghui; Li, Xinbo; Sun, Xiaodong
Combined liquid-phase reduction method and ultrasonic vibration mixing technology, a new method for controllable synthesis of silver nanoparticles (AgNPs) using an acoustofluidic micromixer is proposed. First, the working mechanism of the acoustofluidic micromixer and the basic principle of the liquid-phase reduction method were briefly described. Then, based on the finite element theory, the simulation software COMSOL was utilized to analyze the vibration pattern and acoustic streaming field of the device. Finally, a series of AgNPs synthesis experiments were carried out using a self-made prototype. Controllable synthesis was achieved by adjusting the control parameters of the device and changing the reagent dosage. And the synthesized AgNPs were characterized by UV spectroscopy and transmission electron microscopy (TEM). Simulation and experimental results show that rapid and homogeneous mixing reaction inside a microchannel is demonstrated via the acoustic streaming phenomenon induced by the interdigital transducers (IDT). The driving voltage, reductant, and protectant concentration have significant effects on the synthesis of AgNPs. Ultrasonic vibration combines with a proper protectant dosage can effectively inhibit particle agglomeration and ensure that the synthesized AgNPs have good homogeneity and monodispersity. When the working voltage is 30–40 V and the concentration ratio of reductant to the precursor is 2:1, the quality of the synthesized AgNPs is better. The samples are approximately spherical, without a large number of agglomerates, and high monodispersity. At this point, the average particle size is about 24.4 nm and the deviation is below 5.01 nm. The excellent and fast mixing reaction performance makes the proposed acoustofluidic micromixer a promising candidate for a wide variety of applications.